STRUKTUR BIAYA, TITIK IMPAS, DAN PENDAPATAN USAHATANI PADI DI KECAMATAN SEPUTIH RAMAN KABUPATEN LAMPUNG TENGAH - Geasti Geasti; Dwi Haryono; Muhammad Irfan Affandi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This research aimes to analyze the structure of rice farming cost, Break Event Point (BEP) of income, production and price, in addition to income level of farming rice. The research isconducted by survay method with the numbers of respondent as many as 52 farmers who are selected by simple random sampling. The research location is choosen intentionally in Seputih Raman, Lampung Tengah Regency. Research data was collected in Januari-Februari 2018 and analyzed by descriptive and quantitative analysis. The results showed that the biggest cost component of the production cost structure was harvest costs, labor outside of the family costs, fertilizer costs, and tractor fees. The value of revenue BEP was Rp5,291,805.05/ha, production BEP 1,012.76 kg/ha, and price BEP Rp1,846.84/ha. Total income from rice farming was equal to Rp21,357,297.13/ha and R/C ratio was 2.83 so that the rice farming was profitable and feasible.Key words: BEP, cost structure, income, rice farming